Adored : an It Girl novel - Von Ziegesar, Cecily (New York : Little, Brown and Co., 2009)
As Waverly Academy gets ready for Christmas, Brett Messerschmidt wants a successful holiday party and a kiss from crush Sebastian Valenti, Tinsley Carmichael wants to unwrap her new boyfriend but instead finds out a secret about him, and Jenny Humphrey lands on Tinsley's hit list-- again.
"Poppy."
Ages 15 and up.
Keywords: Teenage girls -- Juvenile fiction; Interpersonal relations -- Juvenile fiction; Wealth -- Juvenile fiction; Boarding schools -- Juvenile fiction; Schools -- Juvenile fiction; Christmas stories; Interpersonal relations -- Fiction; Wealth -- Fiction; Boarding schools -- Fiction; Schools -- Fiction; Christmas -- Fiction; New York (State) -- Juvenile fiction; New York (State) -- Fiction